2002
DOI: 10.1084/jem.20020468
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of HIV-1 Infection of New World Monkey Cells Occurs Primarily at the Stage of Virus Entry

Abstract: HIV-1 naturally infects chimpanzees and humans, but does not infect Old World monkeys because of replication blocks that occur after virus entry into the cell. To understand the species-specific restrictions operating on HIV-1 infection, the ability of HIV-1 to infect the cells of New World monkeys was examined. Primary cells derived from common marmosets and squirrel monkeys support every phase of HIV-1 replication with the exception of virus entry. Efficient HIV-1 entry typically requires binding of the vira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 83 publications
1
36
0
Order By: Relevance
“…A previous study of factors limiting HIV-1 replication in New World primates showed that the CD4 molecules of squirrel monkeys (S. sciureus) and marmosets (C. jacchus) did not support efficient HIV-1 entry. However, alteration of marmoset CD4 residues 48 and 59 to their human counterparts rescued efficient entry of several HIV-1 isolates (13). Arginine 59 of human CD4, in particular, makes a critical salt bridge with aspartic acid 368, highly conserved in the HIV-1 envelope glycoprotein (12).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study of factors limiting HIV-1 replication in New World primates showed that the CD4 molecules of squirrel monkeys (S. sciureus) and marmosets (C. jacchus) did not support efficient HIV-1 entry. However, alteration of marmoset CD4 residues 48 and 59 to their human counterparts rescued efficient entry of several HIV-1 isolates (13). Arginine 59 of human CD4, in particular, makes a critical salt bridge with aspartic acid 368, highly conserved in the HIV-1 envelope glycoprotein (12).…”
Section: Resultsmentioning
confidence: 99%
“…However, to date, no lentiviruses have been isolated from these animals, and neither HIV-1 nor simian immunodeficiency virus replicates in their primary cells. It has been observed that marmoset and squirrel monkey CD4 and CCR5 molecules do not bind HIV-1 gp120 or facilitate viral entry, and it had been suggested that entry is the major restriction to viral replication in most primary New World primate cells (13). Subsequent to these studies, replication of HIV-1 in the owl monkey cell line OMK was shown to be restricted by owl monkey TRIM-cyp, a variant of the rhesus macaque restriction factor TRIM5␣ in which the TRIM5␣ B20.4 domain is replaced by a nearly intact cyclophilin domain (16,18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The susceptibility of various MuLV isolates to Fv1 restriction is largely determined by a single amino acid, residue 110, of the CA protein (34). Very recently, human cells have been shown to exhibit a similar restriction, first dubbed Ref1 activity, which blocks infection by MuLVs very early after infection, even before reverse transcription (29,36). TRIM5␣, a member of the so-called tripartite motif family, has been identified as the protein responsible for this activity (25,33,53,67,75).…”
mentioning
confidence: 99%
“…However, some of these monkeys, like common marmosets, have been frequently used in animal models in other fields and are an attractive prospect for the development of a new animal model of HIV-1 infection. Previous studies have suggested that one major blockade to HIV-1 infection in New World monkeys occurs at the level of viral entry, because HIV-1 envelope glycoproteins cannot effectively bind the CD4 and CCR5 receptors of common marmosets (29). Using a directed-evolution method that takes advantage of the natural ability of the virus to mutate during replication, we were able to generate HIV-1 variants able to replicate in cells expressing the common marmoset receptors CD4 and CXCR4 (30).…”
Section: T He Main Cause Of Aids Is Chronic Infection By Human Immunomentioning
confidence: 82%